Special Needs Families in the Military: A Resource Guide - Moore, Janelle B.; Philpott, Don (Government Institutes, 2011)
The saying 'it takes a village to raise a child' is especially true for families with special needs children. It takes an 'army' of therapists, doctors, nurses, counselors, and educators. Special needs families in the military often find the task even more daunting, compounded by the unique circumstances of military life today. Even though the challenges are often greater, there are many helpful resources for families in the military who are raising a special needs child. In Special Needs Families in the Military: A Resource Guide, authors Janelle Hill and Don Philpott provide advice on the many issues that arise, including diagnoses, financial support, education, medical care, case management, insurance, advocacy, and coping with the accompanying mental and emotional trials. The book covers the basic challenges which all special needs families must face, and also pays special attention to those resources, programs, and aids available to special needs families in the military, where the added stresses of military life often make things seem overwhelming. This book guides special needs families through all the procedures and protocol they must face, and offers helpful tips for setbacks and unexpected challenges that may arise. It is essential reading for military families with special needs children and those who work with them.